A Literature Review on the Separation of Chemical Compounds - Husien, Nemah Sahib Mohammed; Gafel, Rajaa Abd Alameer; Jaffer, Noor Dia (American International Journal of Multidisciplinary Scientific Research, 2018)
This literature involved explanation about separation organic components in mixture such as(chromatography ,extraction ,filtration, centrifuge…) , principles of separation , methods of separation ,types of separation , purification of separated compounds , conditions of separation , physical and chemical properties of mixture.